A revision of the weevil genus Procas Stephens (Coleoptera: Curculionoidea: Erirhinidae) - Thompson, Richard T. (Zootaxa, 2006)
The Holarctic weevil genus Procas Stephens, 1831 is revised for the first time. Six species are recognized: four in the western Palaearctic Region, one in the eastern Palaearctic Region and one in the Nearctic Region. One new species, P. michaelis, sp. n. is described from Spain and one new subspecies, P. picipes levantinus, ssp. n. is described from the Levant. P. picipes (Marsham, 1802), sp. rev. and P. p. steveni (Gyllenhal, 1835), ssp. rev. are released from synonymy with P. armillatus (Fabricius, 1801). The species are separated using, among others, characters derived from sternite 8 of the male which is here used at species level for the first time.        Related genera are discussed. Notodermus Desbrochers, 1875, gen. rev. and Apachiscelus Desbrochers, 1875, gen. rev. are released from synonymy with Procas. Pseudypera Voss, 1936, is returned to synonymy with Notodermus (stat. rev.). Syrdariellia Ter-Minassian, 1978 = Theanellus Reitter, 1912, syn. n. Hypera siccensis (Normand, 1951), comb. n. (ex Procas) = H. pollux (Fabricius, 1796), syn. n. Procas cottyi Perris, 1864 = P. armillatus (Fabricius, 1801), syn. rev. The following new combinations are made in Theanellus: T. alepensis (Pic), comb. n. (ex Procas); T. alternans (Faust, 1885), comb. n. (ex Procas); T. testaceus (Bajtenov, 1974), comb. n. (ex Procas); T. antoinei (Hustache, 1932), comb. n. (ex Procas); T. fastidiosus (Pic, 1904b), comb. n. (ex Procas).        The relationships of the taxa are shown in a simple dendrogram, together with their habitats which vary from very wet to very dry.